Predicting the Raman spectra of ferroelectric phases in two-dimensional Ga2O3 monolayer. Issue 22 (25th May 2022) - Deng, Zexiang
Abstract : We investigate the vibrational properties and Raman spectra of the two-dimensional Ga2 O3 monolayer, using density functional theory. Abstract : We investigate the vibrational properties and Raman spectra of the two-dimensional Ga2 O3 monolayer, using density functional theory. Two ferroelectric (FE) phases of the Ga2 O3 monolayer with wurtzite (WZ) and zinc blende (ZB) structures (FE–WZ and FE–ZB, respectively) are considered. The Raman tensor and angle-dependent Raman intensities of two major Raman peaks (A11 and A21) in both FE–WZ (497, and 779 cm −1 ) and FE–ZB (481, and 772 cm −1 ) Ga2 O3 monolayers, are calculated for the polarization of scattered light, parallel and perpendicular to that of the incident light. The characteristics of angle-dependent Raman intensities are analyzed. The average non-resonant Raman spectra of the minor peaks in FE–WZ (E 1 ) and FE–BZ (E 1 and E 2 ) are compared with those of major peaks A11 and A21. These predictions of the Raman spectra of the Ga2 O3 monolayer may guide the rational design of two-dimensional optical devices.